2007
DOI: 10.1562/0031-8655(2002)0760622sotcid2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Conical Intersections Driving the cis-trans Photoisomerization of Conjugated Molecules¶

Abstract: High‐level ab initio calculations show that the singlet photochemical cis–trans isomerization of organic molecules under isolated conditions can occur according to two distinct mechanisms. These mechanisms are characterized by the different structures of the conical intersection funnels controlling photoproduct formation. In nonpolar (e.g. hydrocarbon) polyenes the lowest‐lying funnel corresponds to a (CH)3 kink with both double and adjacent single bonds twisted, which may initiate hula‐twist (HT) isomerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 72 publications
(129 reference statements)
0
23
0
Order By: Relevance
“…The analysis by Olivucci, Robb, Schlegel, and coworkers [27,[36][37][38][39][40] of the potential energy surfaces of models for retinal protonated Schiff bases (PSBs) and the structurally related cyanines emphasizes the crucial role of the barrier between planar and twisted conformations on the excited state dynamics. The gradients of the potential energy surface near the Franck-Condon geometry are effectively controlled by the conjugation length [27].…”
Section: Potential Energy Surfaces and Vibrational Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis by Olivucci, Robb, Schlegel, and coworkers [27,[36][37][38][39][40] of the potential energy surfaces of models for retinal protonated Schiff bases (PSBs) and the structurally related cyanines emphasizes the crucial role of the barrier between planar and twisted conformations on the excited state dynamics. The gradients of the potential energy surface near the Franck-Condon geometry are effectively controlled by the conjugation length [27].…”
Section: Potential Energy Surfaces and Vibrational Dynamicsmentioning
confidence: 99%
“…Torsional gradients encountered near the planar minimum result in an intramolecular redistribution of the Franck-Condon structure's momentum towards twisted conformations, which promotes crossing of the activation barrier and launching of trajectories leading to the conical intersection [37]. The fluorescence of cyanines and PSBs is largely quenched by crossing to the ground state, either with isomerization or by returning to the original ground state minimum [27,[38][39][40].…”
Section: Potential Energy Surfaces and Vibrational Dynamicsmentioning
confidence: 99%
“…At this point, it is important to recall information on two important CIs related to the photoisomerization of conjugated polyene systems. The first is a crossing between two states having 1A g and 1B u electronic structures (1B u /1A g crossing featuring a single 90° twisted CC bond) and is found in cationic conjugated systems such as rPSB. The second, a crossing between 2A g and 1A g like states (2A g /1A g crossing, also called a (CH) 3 -kinked CI) is found in nonpolar systems …”
mentioning
confidence: 99%
“…The vibrational normal-mode analysis with specified PES involving the steep route indicated that the vibrational mode with frequency 240 cm −1 also strengthens the OBF mechanism [54]. Fuß and coworkers [43,55,56] suggested that the HT and the aborted HT mechanisms were deduced from the systematic features of the cis-and trans-photoisomerizations of nonpolar conjugated molecules and these were investigated by the experimental measurements as well [58][59][60].…”
Section: Introductionmentioning
confidence: 98%
“…The isomerization of cis-and trans-Stilbene has been extensively studied for more than forty years and the quantum yields of the photoisomerization were measured experimentally [39,40]. Three mechanisms were characterized for the isomerization; they are the conventional one-bond flip (OBF) [41], Hula-Twist (HT) [42], and the aborted HT mechanisms [43]. The OBF mechanism involves a 180 ∘ rotation around the central ethylenic C=C bond.…”
Section: Introductionmentioning
confidence: 99%